Produksi dan Bobot Telur Puyuh (Coturnix coturnix japonica) dengan Penambahan Tepung Daun Pepaya (Carica Papaya L.) sebagai Pakan Alternatif: Production and Weight of Quail Eggs (Coturnix coturnix japonica) with Additional Papaya Flour Leaves (Carica papaya L.) as Alternative Feed - Ali, Dahrul; Novieta, Intan Dwi; Fitriani, Fitriani; Mubarak Z, Sultan (Anoa: Journal of Animal Husbandry, 2022)
This study aims to determine the effect of adding flour papaya leaf (Carica papaya L) on egg production and weight in quail by using a completely randomized design (CRD) method with four treatments and three replications. P0: No control treatment 0%. P1: Flour papaya leaves (Carica papaya L) 1% of the amount of feed. P2: Papaya leaf flour (Carica papaya L) 3% of the total feed. P3: Papaya leaf flour (Carica papaya L) 5% of the total feed. The results showed that the addition of leaf flour at different levels had no significant effect (P> 0.05) on egg production while the egg weight had a significant effect (P<0.05). Average egg production P0 (62.5%), P1 (78.12%), P2 (79.16%), P3 (83.33%), Egg weights P0 (8.4%), P1 (9%) P2 (10.13%) and P3 (11.23%). As for the best treatment is in the P3 treatment with the addition of leaf flour papaya as much as 5%